Substantiation of optimal characteristics of the device for electroodontodiagnostics based on the study of complex electrical resistance of tooth tissues - A. G. Volkov; N. Zh. Dikopova; T. A. Amoev; V. M. Grinin; Z. M. Abaev; I. A. Nikolskaya (Эндодонтия Today, 2024)
AIM. Aim of this work is to substantiate the optimal characteristics of the apparatus for electroodontodiagnostics on the basis of studying the complex electrical resistance of tooth tissues.MATERIALS AND METHODS. The study of complex tissue resistance during electroodontodiagnostics in 50 patients aged from 18 to 55 years was carried out. A total of 181 teeth were studied. All the teeth studied were with formed roots. 52 teeth were intact, 40 teeth had been previously treated for caries, 26 teeth had carious process, 21 teeth were diagnosed with pulpitis, 9 teeth were diagnosed with periodontitis, 33 teeth had been previously subjected to endodontic treatment.RESULTS. The results of studying the complex tissue impedance during electroodontodiagnostics showed that the impedance module can be in a wide range from 120 kOhm to 3500 kOhm. At that, the main contribution to the complex impedance is made by the state of hard tissues of teeth.CONCLUSION. The obtained results showed that the device for electroodontodiagnostics should automatically in a continuous mode to measure impedance and according to it to control the supply of the necessary exponentially increasing alternating sinusoidal current with a frequency of 50 Hz.